POLITICAL PROPAGANDA AS AN IDEOLOGICAL COMPONENT OF THE COMMUNICATION PROCESS: THEORETICAL ASPECT - M. K. Alkhazova; A. V. Mankieva; A. K. Botasheva (Современная наука и инновации, 2022)
Political propaganda correlates with the interaction of subjects of the political process in the formation of new attitudes that affect the social or political society behavior. The purpose of propaganda is to transmit political information to the public and influence on its perception, which will provide a general direction of thoughts and actions, a positive or negative attitude to a particular object or certain value.